2016
DOI: 10.15744/2456-5482.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after Pediatric Fundoplication: Defining the Redo Population

Abstract: Objective:The aims were to compare outcome variables in children with gastroesophageal reflux disease (GERD) and one Nissen fundoplication to children with redo fundoplications and define the pediatric redo population. Methods:After IRB approval (#5100277), a case control study was conducted of children younger than 18 years, from two children's hospitals, with one Nissen fundoplication (control group) or a redo performed between January 1995 and March 2011. Complete data were collected by phone calls to careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Almost all patients and parents were satisfied with the outcome of the RF. In contrast, the only other study that has addressed satisfaction after RF in children, found that only 17% of parents were satisfied [13] . One explanation for the discrepancy may be the definition of satisfaction.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Almost all patients and parents were satisfied with the outcome of the RF. In contrast, the only other study that has addressed satisfaction after RF in children, found that only 17% of parents were satisfied [13] . One explanation for the discrepancy may be the definition of satisfaction.…”
Section: Discussionmentioning
confidence: 81%
“…Only one previous study has assessed outcome after RF beyond retrospective chart reviews. In this study including 31 children, family members reported that 61% of the children were back on anti-secretory drugs, and 45% vomited regularly median 3.6 years after the RF [13] . Even more concerning was that only 17% of the parents were satisfied with the outcome of the RF [13] .…”
Section: Introductionmentioning
confidence: 70%